2016
DOI: 10.1371/journal.pone.0156198
|View full text |Cite
|
Sign up to set email alerts
|

Palmitoylethanolamide Modulates Inflammation-Associated Vascular Endothelial Growth Factor (VEGF) Signaling via the Akt/mTOR Pathway in a Selective Peroxisome Proliferator-Activated Receptor Alpha (PPAR-α)-Dependent Manner

Abstract: Background and AimAngiogenesis is emerging as a pivotal process in chronic inflammatory pathologies, promoting immune infiltration and prompting carcinogenesis. Ulcerative Colitis (UC) and Crohn’s Disease (CD) represent paradigmatic examples of intestinal chronic inflammatory conditions in which the process of neovascularization correlates with the severity and progression of the diseases. Molecules able to target the angiogenesis have thus the potential to synergistically affect the disease course. Beyond its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 59 publications
4
31
0
Order By: Relevance
“…As expected, these ALIAmide-induced immunomodulatory activities were mediated by their respective anti-inflammatory receptors, namely PPAR-a and CB 2 . This observation is in line with previous studies showing that PPAR-a mediates most, if not all, antiinflammatory and antinociceptive effects of both OEA and PEA (31,32). However, our findings do not rule out the involvement of other molecular targets of these 2 ALIAmides, including G-protein-coupled receptor (GPR)119 and GPR55, although the latter receptors are expressed in specific tissues only or bear proinflammatory effects.…”
Section: Discussionsupporting
confidence: 86%
“…As expected, these ALIAmide-induced immunomodulatory activities were mediated by their respective anti-inflammatory receptors, namely PPAR-a and CB 2 . This observation is in line with previous studies showing that PPAR-a mediates most, if not all, antiinflammatory and antinociceptive effects of both OEA and PEA (31,32). However, our findings do not rule out the involvement of other molecular targets of these 2 ALIAmides, including G-protein-coupled receptor (GPR)119 and GPR55, although the latter receptors are expressed in specific tissues only or bear proinflammatory effects.…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, the role of PPAR‐α in inflammatory bowel diseases was also studied, and in a mouse model of DSS‐induced ulcerative colitis as well as in cultured human biopsies deriving from patients with ulcerative colitis, PEA treatment improved the macroscopic signs of ulcerative colitis, decreased the expression and release of pro‐inflammatory cytokines as well as neutrophil infiltration (Esposito et al, ), all these anti‐inflammatory effects being abolished by PPAR‐α antagonists (Esposito et al, ). More recently, the effects of PEA on inflammation‐associated angiogenesis in mice with DSS‐induced ulcerative colitis and in patients with ulcerative colitis were also studied (Sarnelli et al, ). PEA treatment, in a PPAR‐α‐dependent manner, inhibited colitis‐associated angiogenesis by decreasing VEGF release and new vessel formation via the mammalian target of rapamycin/PKB (mTOR/Akt) axis (Sarnelli et al, ).…”
Section: Inflammatory Diseasesmentioning
confidence: 99%
“…In line with these results, inhibition of the PEA-degrading enzyme N-acylethanolamine hydrolyzing acid amidase increased PEA levels and also protected against colitis [51]. Furthermore, Sarnelli et al [52] reported that inhibition of inflammation-associated angiogenesis by PEA in a DSS model was dependent on PPARα. Additionally, they showed that the release of vascular endothelial growth factor and the formation of vessels were decreased, leading to a reduction in mucosal damage [52].…”
Section: Insights From Animal Modelsmentioning
confidence: 61%
“…Furthermore, Sarnelli et al [52] reported that inhibition of inflammation-associated angiogenesis by PEA in a DSS model was dependent on PPARα. Additionally, they showed that the release of vascular endothelial growth factor and the formation of vessels were decreased, leading to a reduction in mucosal damage [52]. Recently, the PEA analog adelmidrol was found to exert anti-inflammatory effects that were partly mediated via PPARγ [53].…”
Section: Insights From Animal Modelsmentioning
confidence: 99%